Unequal opportunity : a crisis in America's schools? - Mitchell, Bruce M. (Bergin & Garvey, 2002)
This volume addresses issues of equal opportunity in education and quality of education. Interviews were conducted with a cross-section of Americans who responded to a questionnaire, and their responses are included and discussed in the book.